Orifice Plates and Venturi Tubes - Reader-Harris, Michael (Experimental Fluid Mechanics, 2015)
This book gives the background to differential-pressure flow measurement and goes through the requirements explaining the reason for them. For those who want to use an orifice plate or a Venturi tube the standard ISO 5167 and its associated Technical Reports give the instructions required.  However, they rarely tell the users why they should follow certain instructions.  This book helps users of the ISO standards for orifice plates and Venturi tubes to understand the reasons why the standards are as they are, to apply them effectively, and to understand the consequences of deviations from the standards.